Mechanical stress protects against osteoarthritis via regulation of the AMPK/NF‐κB signaling pathway. Issue 6 (12th October 2018) - Yang, Yue; Wang, Yang; Kong, Yawei; Zhang, Xiaoning; Zhang, He; Gang, Yi; Bai, Lunhao
Abstract: Mechanical stress plays a key role in regulating cartilage degradation in osteoarthritis (OA). The aim of this study was to evaluate the effects and mechanisms of mechanical stress on articular cartilage. A total of 80 male Sprague‐Dawley rats were randomly divided into eight groups ( n  = 10 for each group): control group (CG), OA group (OAG), and CG or OAG subjected to low‐, moderate‐, or high‐intensity treadmill exercise (CL, CM, CH, OAL, OAM, and OAH, respectively). Chondrocytes were obtained from the knee joints of rats; they were cultured on Bioflex 6‐well culture plates and subjected to different durations of cyclic tensile strain (CTS) with or without exposure to interleukin‐1β (IL‐1β). The results of the histological score, immunohistochemistry, enzyme‐linked immunosorbent assay, and western‐blot analyses indicated that there were no differences between CM and CG, but OAM showed therapeutic effects compared with OAG. However, CH and OAH experienced more cartilage damage than CG and OAG, respectively. CTS had no therapeutic effects on collagen II of normal chondrocytes, which is consistent with findings after treadmill exercise. However, CTS for 4 hr could alleviate the chondrocyte damage induced by IL‐1β by activating AMP‐activated protein kinase (AMPK) phosphorylation and suppressing nuclear translocation of nuclear factor (NF)‐κB p65. Our findings indicate that mechanical stress had no therapeutic effects on normal articular cartilage and chondrocytes; mechanical stress only caused damage with excessive stimulation. Still, moderate biomechanical stress could reduce sensitization to the inflammatory response of articular cartilage and chondrocytes through the AMPK/NF‐κB signaling pathway. Abstract : Our findings indicate that mechanical stress had no therapeutic effects on normal articular cartilage and chondrocytes; mechanical stress only caused damage with excessive stimulation. Still, moderate biomechanical stress could reduce sensitization to the inflammatory response of articular cartilage and chondrocytes through the AMP‐activated protein kinase (AMPK)/nuclear factor (NF)‐κB signaling pathway.